Incorporating water isoscapes in hydrological and water resource investigations. (16th February 2015) - Bowen, Gabriel J.; Good, Stephen P.
Abstract : Water cycle science is confronted with the critical challenge of understanding sources, pathways, and processes that govern the availability of water and its interaction with biogeochemical cycles across a range of Earth systems. These problems are inherently spatial in nature, and require observational tools that can establish connectivity within the water cycle, quantify processes affecting water cycling across scales, and provide robust tests of hydrological models. Spatial analysis of water H and O isotope data has recently emerged as a valuable approach to such problems. Isotope distributions in hydrological systems are associated with variation in water sources, upstream processes that fractionate isotopes along transport trajectories, and local conditions that govern partitioning of water among pools and fluxes. Data products and models that represent spatiotemporal isotope distributions (isoscapes) provide a basis for using isotopes in quantitative spatial hydrology research. The potential of this work, as well as current limitations, is reflected in recent case studies focused on atmospheric, land surface, groundwater, and managed systems. Many of limitations, stemming from challenges associated with data availability and spatiotemporal resolution, should be reduced in the future as new sample networks, improved instrumentation, more sophisticated data analysis approaches, and enhanced data sharing emerge. These advances will increase the accessibility of isoscape applications and their relevance to a wide range of hydrological and water resource problems. WIREs Water 2015, 2:107–119. doi: 10.1002/wat2.1069 This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water Quality